Knowledge of and Attitude Towards Epilepsy Among Women in Ile-Ife, Nigeria - Fehintola, Funmito O.; Olowookere, Samuel A.; Adegbenro, Caleb A.; Afolabi, Temitope O.; Oladapo, Victor; Oladimeji, Akinyele O.; Oladipo, Opeyemi E.; Olagunju, Olayinka R.; Olajide, Ademola A. (Sudan Journal of Medical Sciences, 2019)
Background: Epilepsy is a non-contagious chronic disease with sufferers experiencing embarrassments amidst other challenges. Family caregivers are mainly women with some of them suffering from the disease. This study assessed the knowledge and attitude of women residents in an urban community towards epilepsy. Materials and methods: This descriptive cross-sectional study recruited 400 randomly selected women in Ile-Ife. The data was collected with the use of a pre-tested interviewer-administered questionnaire on knowledge of and attitude to epilepsy. Data was analysed using descriptive and inferential statistics. Results: Most respondents (99.3%) were aware of the disease with their main sources of information from their parents, friends, and neighbours. Only 15.3% of respondents had good knowledge of epilepsy, while 35% had positive attitude to epilepsy. Factors associated with good knowledge of epilepsy among respondents include having higher education (OR = 3.154, 95%CI = 1.574–6.323, p = 0.001) and higher income (OR = 3.055, 95%CI = 1.404–6.651, p = 0.005), while factors associated with positive attitude towards epilepsy include older age group (OR = 1.943, 95%CI = 1.281–2.945,p = 0.002) and higher income (OR = 2.932, 95%CI = 1.345–6.386, p = 0.007). Conclusions: Although the level of awareness is high, respondents’ knowledgeand attitude were inadequate. There is a need for a community education about epilepsy, targeting women who are major stakeholders with the aim of improving their knowledge and attitude towards the disease.